The Sentinel Lymph Node in Breast Cancer: Problems Posed by Examination During Surgery. A Review of Current Literature and Management - Bouquet de Jolinière, Jean; Major, A.; Khomsi, F.; Ben Ali, N.; Guillou, L.; Feki, A. (Frontiers in Surgery, 2018)
The presence of tumor cells can be identified in the lymph node when metastasis has occurred from the primary cancer site into the lymph node. If the sentinel lymph node ganglion is negative for the presence of tumor cells at the time of histological examination, the other lymph nodes are also negative in 99% of cases. If no tumor cells are identified in the sentinel lymph node ganglion by histological examination, the other lymph nodes are also negative for the presence of tumor cells in 99% of cases. The sentinel lymph node advantageously replaces axillary dissection as a staging method in breast cancer T1 and T2. Approximately 40% of breast cancers metastasize to axillary lymph nodes and metastatic extension depends on disease stage. Sentinel lymph nodes are affected in the following stages: T1a (4.3 %), T1b (19.5 %), T1c (23.8 %), T2 (48.9 %), T3 (66.7 %).